„Odciąć głupocie tlen”: o niepostmodernistycznym wątku w eseistyce Wiktora Jerofiejewa - Stryjakowska, Anna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article describes Victor Erofeyev’s essay Love for stupidity, in which the Russianpostmodernist comes up with an uncompromising objection to the mass culture. The defence of high literature as an existential signpost leading to timeless values is placed by the author in the socio-political context of modernization challenges faced by contemporaryRussia. Alongside highlighting this less familiar theme of Erofeyev’s works the analysis aims at drawing attention to the aporias in the writer’s considerations as well as confronting the essay with another sketches devoted to the changes of literary life in the conditions of the consumer society.